2000
DOI: 10.1093/nar/28.5.1193
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence analysis by hybridization with oligonucleotide microchips: MALDI mass spectrometry identification of 5mers contiguously stacked to microchip oligonucleotides

Abstract: Matrix-assisted laser desorption ionization mass spectrometry (MALDI MS) has been applied to increase the informational output from DNA sequence analysis. It has been used to analyze DNA by hybridization with microarrays of gel-immobilized oligonucleotides extended with stacked 5mers. In model experiments, a 28 nt long DNA fragment was hybridized with 10 immobilized, overlapping 8mers. Then, in a second round of hybridization DNA-8mer duplexes were hybridized with a mixture of 10 5mers. The stability of the 5m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
0
25
0
1
Order By: Relevance
“…In addition to precise identification of bound compounds, MALDI spectrometers are potentially high-throughput devices. Taking into account the large capacity of gel pads as compared with solid-phase immobilization, we investigated the possibility of analyzing pentamers bound to target sequences within the gel pads by MALDI MS [Stomakhin et al, 2000]. The binding of the 5-mers with the existing partially single-stranded structure, the so-called contiguous stacking hybridization (CSH; Fig.…”
Section: Data Acquisition: Maldi Msmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to precise identification of bound compounds, MALDI spectrometers are potentially high-throughput devices. Taking into account the large capacity of gel pads as compared with solid-phase immobilization, we investigated the possibility of analyzing pentamers bound to target sequences within the gel pads by MALDI MS [Stomakhin et al, 2000]. The binding of the 5-mers with the existing partially single-stranded structure, the so-called contiguous stacking hybridization (CSH; Fig.…”
Section: Data Acquisition: Maldi Msmentioning
confidence: 99%
“…1A), is defined by the interaction between the terminal bases of incoming oligonucleotides with the already hybridized oligonucleotide. In their model experiments, Stomakhin and his coworkers [Stomakhin et al, 2000] analyzed a 28-nucleotide long sequence. Ten gel pads (1 × 1 × 0.02 mm) were placed in a linear arrangement on an electrically conductive silicon chip.…”
Section: Data Acquisition: Maldi Msmentioning
confidence: 99%
“…Kutyavin et al (2000) used minor-groove-binding molecules that stabilize properly formed double helices. Yershov et al (1996), Stomakhin et al (2000), and MaldonadoRodriquez et al (1999) described methods whereby duplexes with properly matched ends are stabilized by the phenomenon of contiguous base stacking. It has also been reported that this level of discrimination can be achieved by hybridizing DNA to a PNA (peptide nucleic acid) array, because of the higher mismatch sensitivity of DNA-PNA binding compared to DNA-DNA binding (Weiler et al 1997;Igloi 1998;Ratilainen et al 2000).…”
Section: Accounting For Mismatchesmentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46] Com este propósito, diferentes configurações de interfaces já foram desenvolvidas, tal como acoplamento em linha com MALDI-MS. [47][48][49] Jin et al 50 apresentaram um trabalho revolucionário construindo um sistema de reator enzimático em linha no qual a bomba seringa, tradicionalmente usada para gerar o fluxo hidrodinâmico, foi substituída pelo fluxo eletroosmótico, levando as proteínas até o reator enzimático. As enzimas foram imobilizadas em uma fase estacionária e neste sistema foi possível, em uma única etapa, promover a digestão de proteínas em 12 min com um sistema integrado de eletroforese na forma de um chip e sua caracterização em um sistema MALDI-TOF-TOF (time of flight).…”
Section: Introductionunclassified